Application of radioimmunoassay to study the reproductive efficiency and performance of indigenous goats in Uganda - Epelu-Opio, J. (1989)
A study was conducted to assess the application of progestrone radioimmunoassay to study the reproductive efficiency and performance of indiginous goats in Uganda. The study revealed mean gestation period of 146.6±30 days (range 143-153 days) for does involved. Out of 33 kiddings 27(81.8%) were singles and 6 (12.2%) were twins. On the day of oestrus or breeding the plasma progestrone concentration was invariably less than 1.0 nmol/l, being zero in >90% of the cases. The mean progestrone level from day 1 post-breeding to parturition was 20.4±9.48 nmol/l (n=859). Mean length of postpartum anoestrus was 148.4±64.90 days (range 60-260 days). Puberty was attained at the age of 250.6±44.67 days (range 160-300) with mean body weight recorded to be 15.3±1.85 kg (range 13-18 kg)(n=11). Two distinct oestrus cycle catagories were identified. The one, which had mean length of 25.7±6.21 days (range 16-35 days), had the highest plasma progestrone concentration of 2.9±1.36 nmol/l (1.0-6.0 nmol/l). False or anovulatory oestrus was common. Inaddition causes of cyclicity variation were indicated. It was concluded that the assay had overall simplicity and practicability and this makes the kits suitable for application in research as well as veterinary diagnosis.